Solitary bees — pollinators of seed alfalfa in the north-east of Ukraine: current state and use in pollination - Filatov, M. O.; Lezhenina, I. P.; Meshkova, V. L.; Polchaninova, N. Yu.; Stankevych, S. V. (The Kharkiv Entomological Society Gazette, 2023)
The data on the species composition of seed alfalfa pollinators, their trophic links, seasonal dynamics, and influence on alfalfa seed productivity were generalized. Among 47 solitary bee species of 15 genera and 6 families, 8 species comprised 87.9% of all bees visiting alfalfa flowers. These species have the highest abundance from the second half of June to the third decade of July, which coincides with the yellow alfalfa flowering after moving at the beginning of the budding stage. The average degree of pollination of alfalfa flowers was 25.4%, which delivers an average of 7.6 centner/ha of actual seed yield in commercial crops. 1 fig., 3 tabs, 57 refs.